1B.04: WHITE COAT PHENOMENON CRUCIALLY AFFECTS CENTRAL BLOOD PRESSURE VALUES. (June 2015) - Tanaka, S.; Murai, S.; Sugiura, T.; Yamashita, S.; Ohte, N.; Dohi, Y.
Abstract : Objective: Although blood pressure measured over the brachial artery is a powerful predictor of cardiovascular morbidity and mortality, recent studies suggest that central blood pressure is more closely associated with cardiovascular events and target organ damage than brachial blood pressure. The present study was designed to investigate effects of white coat phenomenon on central blood pressure. Design and method: Outpatients with essential hypertension who were under antihypertensive medication with a stable blood pressure control at least for the last 6 months (n = 50, 70 ± 14 years) were recruited. They were instructed to measure blood pressure by themselves in the morning at home (home blood pressure). At medical examination, brachial blood pressure (oscillometer) and radial artery pressure waveforms (tonometer) were recorded using an automated device, and central blood pressure was estimated using systolic pressure corresponding to the second systolic peak of radial pressure waveforms (HEM-9000AI, Omron Healthcare, Kyoto). White coat phenomenon was quantified by the following formula: [(office blood pressure) – (home blood pressure)]/ (home blood pressure). Results: Estimated central blood pressure correlated with both office blood pressure (r = 0.86, p < 0.001) and home blood pressure (r = 0.53, p < 0.01), but the relationship of central blood pressure with office blood pressure was somewhat closer as compared to that with home blood pressure. A correlation was observed between central blood pressure and white coat phenomenon (r = 0.44, p < 0.05). In multiple regression analysis, white coat phenomenon was an independent predictor of central blood pressure. Conclusions: Office blood pressure may have greater impact on central blood pressure than self-measured home blood pressure. Although central blood pressure may be a good marker of cardiovascular events and target organ damage, possible effects of white coat phenomenon should be considered when interpreting central blood pressure values.